Toward a Legislative Framework for Traditional and Complementary Medicine in Africa: A Legal Commentary on Ghana and the Gambia - (:unkn) unknown (My University, 2025)
Background: Africa’s healthcare systems are inherently pluralistic, with Traditional and Complementary Medicine (TCAM) playing a central role in public health. However, despite constitutional recognition of indigenous healing systems in countries such as Ghana and The Gambia, regulatory frameworks remain narrow, outdated, or entirely absent—failing to reflect the evolving role of Complementary and Alternative Medicine (CAM) modalities such as naturopathy, homeopathy, and Ayurveda. Aim of the Study: This study aims to examine the constitutional and legal foundations of TCAM in Ghana and The Gambia, identify existing regulatory gaps, and propose a harmonized and inclusive legislative framework that ensures professional recognition and governance autonomy for both traditional and CAM practitioners. Methodology and Methods: This study employed a doctrinal and comparative legal research approach. It involved critical analysis of key constitutional provisions, including Articles 11(3) and 26(2) of the 1992 Constitution of Ghana and Section 7 of the 1997 Constitution of The Gambia. Relevant statutory instruments and policy documents were also examined, such as Ghana’s Traditional Medicine Practice Act 575 and The Gambia’s Draft Traditional Health Practitioners Bill, 2025. Additionally, international frameworks—particularly the WHO Traditional Medicine Strategy 2014–2023—and national policy drafts like The Gambia’s 2020 Draft Constitution were reviewed to contextualize the legal positioning of traditional medicine within broader global and regional governance structures. Results and Findings: The study found that both Ghana and The Gambia have constitutional backing for traditional medicine, yet existing laws—such as Ghana’s Traditional Medicine Practice Act (Act 575)—are limited in scope, excluding CAM systems that are increasingly relevant. The Gambia lacks a comprehensive TCAM statute entirely. The findings support the need for a dual
Keywords: African Research